2013
DOI: 10.1101/gad.224568.113
|View full text |Cite
|
Sign up to set email alerts
|

ATR–Chk1–APC/CCdh1-dependent stabilization of Cdc7–ASK (Dbf4) kinase is required for DNA lesion bypass under replication stress

Abstract: Cdc7 kinase regulates DNA replication. However, its role in DNA repair and recombination is poorly understood. Here we describe a pathway that stabilizes the human Cdc7-ASK (activator of S-phase kinase; also called Dbf4), its regulation, and its function in cellular responses to compromised DNA replication. Stalled DNA replication evoked stabilization of the Cdc7-ASK (Dbf4) complex in a manner dependent on ATR-Chk1-mediated checkpoint signaling and its interplay with the anaphase-promoting complex/cyclosome Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 71 publications
6
99
0
Order By: Relevance
“…The bestcharacterized ATR effector, to date, is Chk1 (Zhao and PiwnicaWorms, 2001), which is activated through ATR-mediated phosphorylation at residues S317 and S345 (Liu et al, 2000) in a reaction that is stimulated by claspin binding to Chk1 (Lindsey- Boltz et al, 2009), by the 9-1-1 complex (Liu et al, 2012;Wang et al, 2006) and RHINO (Lindsey-Boltz et al, 2015), as well as by other factors (Nam and Cortez, 2011) (see poster). Chk1 activation stabilizes the chromatin-bound CDC7-DBF4 apoptosis signalregulating kinase (ASK) complex, which assists in replication and origin firing (Yamada et al, 2013). Chk1 affects progression through S phase at the level of origin firing, replication elongation and fork integrity (Brown and Baltimore, 2003;Heffernan et al, 2007;Petermann et al, 2006Petermann et al, , 2010Segurado and Diffley, 2008;Zhao et al, 2002).…”
Section: Atr In Cell Cycle Regulationmentioning
confidence: 99%
“…The bestcharacterized ATR effector, to date, is Chk1 (Zhao and PiwnicaWorms, 2001), which is activated through ATR-mediated phosphorylation at residues S317 and S345 (Liu et al, 2000) in a reaction that is stimulated by claspin binding to Chk1 (Lindsey- Boltz et al, 2009), by the 9-1-1 complex (Liu et al, 2012;Wang et al, 2006) and RHINO (Lindsey-Boltz et al, 2015), as well as by other factors (Nam and Cortez, 2011) (see poster). Chk1 activation stabilizes the chromatin-bound CDC7-DBF4 apoptosis signalregulating kinase (ASK) complex, which assists in replication and origin firing (Yamada et al, 2013). Chk1 affects progression through S phase at the level of origin firing, replication elongation and fork integrity (Brown and Baltimore, 2003;Heffernan et al, 2007;Petermann et al, 2006Petermann et al, , 2010Segurado and Diffley, 2008;Zhao et al, 2002).…”
Section: Atr In Cell Cycle Regulationmentioning
confidence: 99%
“…Since blocking DDK activity largely prevents CHK1 phosphorylation upon exposure to replication stress [14,16, 17], we analyzed how DDK influences the overall checkpoint response induced by HU. We found that 5 µM of DDKi and a pre-treatment time of 4 hours were required to substantially block CHK1 activation by HU in HCC1954 cells (Supplementary Figure 1A).…”
Section: Ddk Has a Primary Role In Initiating Replication Checkpoint mentioning
confidence: 99%
“…However, subsequent studies reported that human DDK is active during replication stress and has an upstream role to fully activate the checkpoint kinase CHK1 [13,14]. In response to exogenous replication inhibitors, DDK recruitment to chromatin is increased [13,14], CDC7-DBF4 complex is stabilized [13], and MCM shows increased phosphorylation at several DDK-specific sites [13,15]. DDK promotes CHK1 phosphorylation partly through binding to and phosphorylating Claspin, an adaptor protein required for CHK1 activation [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current report, we infer that DDK must be active during DNA damage checkpoint activation to allow for TLS. Similarly, human DDK on chromatin remains active during checkpoint activation to facilitate TLS by Polh (Yamada et al 2013). It was proposed there are two distinct pools of DDK with the soluble pool inhibited to block late origin firing, while the chromatinbound pool remains active to facilitate TLS (Yamada et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on biochemical analyses, we suggest DDK regulates mutagenesis by direct interaction with and phosphorylation of the Rev7 subunit of Polz. Our results are important, given the conservation of DDK's role in TLS in human cells (Day et al 2010;Yamada et al 2013), and are significant with regard to human disease because overexpression of yeast DDK increases mutagenesis (Sclafani et al 1988;Sclafani and Jackson 1994), human DDK overexpression is observed in many types of cancer cells (Hess et al 1998;Nambiar et al 2007;Bonte et al 2008;Clarke et al 2009;Kulkarni et al 2009), and DDK is a therapeutic target in cancer patients (Rodriguez-Acebes et al 2010).…”
mentioning
confidence: 99%